Impact of CRM Strategy on the Growth of Online Retail in India (International Journal of Food and Nutritional Sciences, 2022)
India has a vast retail industry. Raise in technology made retailers in India move to onlinestores that retreated CRM. An increase in the competition and demand of customers alsoasked for CRM. All the retailers started finding innovative solutions and implementing themto retain their customers. CRM is needed to maintain a good relationship with customers tosustain a competitive environment. Comprehending and meeting the expectation of customerswill help in having a good and long relationship with the customers. Maintaining goodrelations with customers increases the number of potential customers, further increasinggrowth. CRM acts as a very effective method in marketing and holding their customers. CRMtools require continuous monitoring to get good engagement with customers.This study aims to provide a detailed analysis of the importance of CRM strategy in Onlineretail markets in India.